Study of antihyperglycaemic activity of medicinal plant extracts in alloxan induced diabetic rats - Anoja P Attanayake; Kamani A. P. W. Jayatilaka; Chitra Pathirana; Lakmini K. B. Mudduwa (Ancient Science of Life, 2013)
Background: Diabetes mellitus, for a long time, has been treated with plant derived medicines in Sri Lanka. Aim: The aim of this study is to determine the efficacy and dose response of oral antihyperglycaemic activity of eight Sri Lankan medicinal plant extracts, which are used to treat diabetes in traditional medicine in diabetic rats. Materials and Methods: Medicinal plants selected for the study on the basis of documented effectiveness and wide use among traditional Ayurveda physicians in the Southern region of Sri Lanka for the treatment of diabetes mellitus. The effect of different doses of aqueous stem bark extracts of Spondias pinnata (Anacardiaceae), Kokoona zeylanica (Celastraceae), Syzygium caryophyllatum (Myrtaceae), Gmelina arborea (Verbenaceae), aerial part extracts of Scoparia dulcis (Scrophulariaceae), Sida alnifolia (Malvaceae), leaf extract of Coccinia grandis (Cucurbitaceae) and root extract of Languas galanga (Zingiberaceae) on oral glucose tolerance test was evaluated. A single dose of 0.25, 0.50, 0.75, 1.00, 1.25, 2.00 g/kg of plant extract was administered orally to alloxan induced (150 mg/kg, ip) diabetic Wistar rats (n = 6). Glibenclamide (0.50 mg/kg) was used as the standard drug. The acute effect was evaluated over a 4 h period using area under the oral glucose tolerance curve. Statistical Analysis: The results were evaluated by analysis of variance followed by Dunnett′s test. Results: The eight plant extracts showed statistically significant dose dependent improvement on glucose tolerance (P < 0.05). The optimum effective dose on glucose tolerance for six extracts was found to be 1.00 g/kg in diabetic rats with the exception of C. grandis: 0.75 g/kg and L. galanga: 1.25 g/kg. C onclusion: The aqueous extract of G. arborea, S. pinnata, K. zeylanica, S. caryophyllatum, S. dulcis, S. alnifolia, L. galanga and C. grandis possess potent acute antihyperglycaemic activity in alloxan induced diabetic rats.